2014
DOI: 10.1038/jp.2014.194
|View full text |Cite
|
Sign up to set email alerts
|

Methadone versus morphine for treatment of neonatal abstinence syndrome: A prospective randomized clinical trial

Abstract: Methadone had a shorter length of neonatal withdrawal treatment compared with morphine. Owing to the smaller sample size and single site, a larger randomized study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 35 publications
4
62
0
1
Order By: Relevance
“…However, this body of literature demonstrates tremendous variability; infants treated with morphine may be treated as long as 37 days or as short as 12 days. 9,[23][24][25] This variation supports the theory that the environment of care is likely more important than the medication used for treatment. Two recent multicenter Ohio collaborative reports and a single-center study in NICUs showed a decreased LOS to between 18 and 23 days with use of a standardized weaning protocol.…”
Section: Figuresupporting
confidence: 61%
“…However, this body of literature demonstrates tremendous variability; infants treated with morphine may be treated as long as 37 days or as short as 12 days. 9,[23][24][25] This variation supports the theory that the environment of care is likely more important than the medication used for treatment. Two recent multicenter Ohio collaborative reports and a single-center study in NICUs showed a decreased LOS to between 18 and 23 days with use of a standardized weaning protocol.…”
Section: Figuresupporting
confidence: 61%
“…2,6 Data suggest that hospitals vary in identification 8 and management 7,8 of infants with NAS. There have been several innovations over the last decade in the management of opioid-dependent mothers 13 and infants with NAS, 14,15 but it is unclear how broadly these innovations have been adopted. In 2012, the AAP issued a policy statement focused on management of substance-exposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, Maine (Alexander et al, 2004;Brown et al 2015;Grau et al, 2007;Heimer et al, 2012;Martin & Rocque, 2011;McCall et al, 2013;Roche, 2000;Rosenberg, 2002;Sorg & Greenwald, 2003) has played a prominent role in this national opioid epidemic (Center for Behavioral Health Statistics and Quality, 2015;Johnston et al, 2015;Maxwell, 2011;Patrick et al, 2015;Paul et al, 2014;Warner et al, 2011). The total daily opioid dose in morphine equivalents in the United States was highest in Maine (798 mg/person), which was approximately fourfold higher than that in the lowest state.…”
mentioning
confidence: 99%